Racial/ethnic status, gender and social mobility in Bogota, Cali and thirteen metropolitan areas of Colombia: a descriptive and econometric analysis - Viáfara López, Carlos Augusto; Estacio Moreno, Alexander; González Aguiar, Luisa María (Sociedad y Economía, 2010)
This article examines intergenerational educational mobility for black middle classes in Bogotá, Cali and the total of the thirteen metropolitan areas. This work uses mobility tables, models of first-order Markov and probability transition matrices. The findings show that afrocolombian middle classes facing greater immobility compared to the no afrocolombian middle classes. This suggests the presence of racial/ethnic discrimination in general, but with stronger effects in Bogotá.